Sharpening the focus of the church - Getz, Gene A. (Chicago : Moody press, 1979)
A splendid analysis of true scriptural ministry of the church, using helpful charts and summaries.
Introduction : from theory to practice -- Church renewal in perspective -- A look through three lenses -- Why the church exists -- Making disciples -- Principles of new testament evangelism -- Building the church -- Vital new testament experiences -- Principles of new testament edification -- Leadership in the new testament church-phase one -- Leadership in the new testament church-phase 2 -- The functioning body -- Principles of new testament leadership -- Biblical examples of administration and organization -- Principles of biblical administration and organization -- Communication in the new testament -- Principles of new testament communication -- Institutionalism in history -- Reflections of institutionalism in the evangelical church -- Cultural implications for the twentieth-century church -- Developing proper perspective-step by step -- Formulating objectives, goals, and standards.
Includes bibliographical references.
Keywords: Church; Church renewal; Theology, Practical; Church; Church renewal; Theology, Practical